“Nós não somos a porta, somos a raiz que fica enterrada e ninguém vê, só passa por cima”: vivências de trabalho de agentes comunitários de saúde em um município do interior do Ceará - Dedê, Dária Maria Barbosa (2024)
This study aimed to understand the work experiences of community health agents in a municipality in the interior of Ceará. To achieve this, it utilized the theoretical and methodological framework of work psychodynamics. This approach, a branch of work clinic studies, analyzes the work context, enabling research and interventions related to work-related suffering. It seeks to create spaces for listening and speaking, with a perspective of mobilization and emancipation of workers. Therefore, it is an approach aimed at understanding the work context with a view toward its transformation. Among the main theoretical categories studied are: pleasure-suffering experiences, defensive strategies, real work, practical intelligence, and recognition. Methodologically, this was a qualitative study that employed collective sessions with community health agents from the municipality of Groaíras as a data collection tool. To ensure ethical considerations, data collection only occurred after approval by the Research Ethics Committee. Data analysis was performed using the analysis of meaning cores technique. The results revealed that the prescribed work for community health agents is characterized by broad and imprecise guidelines, which can weaken work organization and thus open space for the decharacterization of their role as agents of social transformation. Consequently, workers continuously strive to use their practical intelligence to perform their work and gain recognition. However, many factors influence with this recognition process, leading to psychological strain and suffering. Finally, it is considered that promoting a discussion space about the work provided to community health agents contributed to strengthening bonds and indicated a sign of subjective mobilization within the worker collective.